OPTIMALISASI TERTIB ADMINISTRASI DI DESA LAWANG AGUNG KECAMATAN AIR PERIUKAN KABUPATEN SELUMA PROVINSI BENGKULU - Adriadi, Rekho (Universitas Muhammadiyah Bengkulu, 2019)
Abstract: Administrative discipline is the process of administrative governance in village government. Lawang Agung Village became a pilot village related to the orderly administration of the village and Lawang Agung village won the best first prize in Bengkulu Province. This study focuses on finding out how to implement orderly administration in the village of Lawang Agung, Air Periukan District, Seluma Regency, Bengkulu Province. The research method used is a descriptive qualitative research method. In this study the data used are primary data and secondary data. Data collection techniques namely interviews, observation, and documentation. The data analysis technique used is the data collection stage, the data reduction stage, the data presentation stage, and drawing conclusions. The results of this study explain that the administration of orderly administration in the village of Lawang Agung, Air Periukan Subdistrict, Seluma Regency, Bengkulu Province, is seen from the elements of organizational governance, communication, financial management and public relations that have been implemented properly. That is, the orderly implementation of village administration has been carried out optimally. However, there is one element of finance that has not been done optimally due to budget constraints so not all proposals from the public can be implemented.